The Effect of Temperature Variations on Sheet Press Machines on the Hardness and Toughness of PP (Polypropylene) and HDPE (High Density Polyethylene) Materials - Winda Sanni Slat; Steven Johny Runtuwene; Djefry Hosang; Agnes Wakkary; Yenni Sigalingging (Asosiasi Dosen Muda Indonesia, 2025)
Global plastic waste continues to grow, making recycling essential for supporting a circular economy. Process parameters, especially heating temperature during sheet pressing, strongly influence the quality of recycled products. Objective: This study investigates how heating temperature affects the impact toughness and hardness of recycled Polypropylene (PP) and High-Density Polyethylene (HDPE) produced using a sheet press machine, and identifies the optimal processing temperature for improved mechanical performance. Methodology: This research used a quantitative experimental approach. Recycled PP and HDPE were shredded, then heated at 160°C, 170°C, 180°C, and 190°C for 120 minutes, and molded into sheet specimens using a sheet press machine. Mechanical properties were evaluated using Charpy impact testing in accordance with ASTM D6110 and Rockwell hardness testing (M scale) following ASTM D785. Results were compared across temperature variations to determine performance trends. Findings: Both materials showed improved impact toughness and hardness as temperature increased up to 180°C, indicating better melt uniformity, fewer voids, and stronger molecular bonding. For HDPE, impact toughness increased from 2.3 J at 160°C to 8.675 J at 170°C, reaching its peak at 180°C, then decreased at 190°C, suggesting early thermal degradation. For PP, the highest average hardness was 15.52 HRM at 180°C, followed by a decline at 190°C, consistent with structural softening and reduced crystallinity. Implications: The results suggest that controlling heating temperature particularly around 180°C can enhance the manufacturing efficiency and product quality of recycled plastic sheets, supporting more reliable and sustainable material utilization. Originality: This study provides practical evidence on the temperature–property relationship for sheet-pressed recycled PP and HDPE under controlled heating conditions and confirms 180°C as an optimal temperature before thermal damage reduces structural integrity.